2011
DOI: 10.1142/s0218348x1100535x
|View full text |Cite
|
Sign up to set email alerts
|

3d Fractal Dimension and Flow Properties in the Pore Structure of Geological Rocks

Abstract: Three-dimensional pore structure of four samples of geological rock was obtained using serial sectioning. Their fractal and flow properties have been successfully determined through image analysis. The measured 3D box counting fractal dimension of four geological rock samples are 2.59, 2.88, 2.88 and 2.29, which are not integer dimensions. This would imply that the structure of the four geological rock samples is fractal in nature. Porosity of the four rock samples are ranged from 0.18 to 0.31 and the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
0
8
0
4
Order By: Relevance
“…Penelitian mengenai struktur pori telah banyak dikembangkan, salah satunya mengenai sifat aliran pada struktur pori dari batuan geologi [1]. Salah satu parameter fisis yang digunakan untuk menganalisis struktur pori pada medium berpori adalah tortuositas.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian mengenai struktur pori telah banyak dikembangkan, salah satunya mengenai sifat aliran pada struktur pori dari batuan geologi [1]. Salah satu parameter fisis yang digunakan untuk menganalisis struktur pori pada medium berpori adalah tortuositas.…”
Section: Pendahuluanunclassified
“…Pelacakan jalur pori terhubung diterapkan pada 5 model uji dan kedua sampel tersebut dilakukan dengan Simple Neurite Tracer yang telah diimplementasikan dalam perangkat lunak Fiji. Selain Simple Neurite Tracer terdapat metode lain untuk pelacakan jalur aliran fluida yaitu Cubical Full Random Walk yang telah digunakan oleh Selly [1]. Metode perhitungan tortuositas yang digunakan adalah metode yang dipakai oleh Dougherty [7] untuk menganalisis tortuositas dari pembuluh darah.…”
Section: Metode Penelitianunclassified
“…Kompleksitas medium dianalisis dengan menghitung terlebih dahulu tortuositas jalur aliran pro terhubung. Jalur aliran dilacak dengan metode cubical full random walk yang telah dikembangkan oleh Fauzi dan Ariwibowo [13] yang kemudian dikembangkan oleh Feranie dkk [12]. Nilai tortuositas dari jalur yang sudah terlacak tersebut dihitung dari perbandingan dari panjang lintasan yang terbentuk oleh pori L' dengan panjang sisi medium L. Perhitungan tortuositas (τ) dapat dilakukan dengan menggunakan Persamaan (1).…”
Section: Metode Penelitianunclassified
“…Dalam berbagai studi mengenai medium berpori khususnya batuan, analisis citra digital digunakan untuk mengetahui karakteristik struktur pori karena eksperimen dalam hal pengkajian kompleksitas aliran fluida pada medium berpori akan lebih mudah dilakukan [4][5][6][7][8][9][10][11][12][13]. Misalnya saja, telah diketahui bahwa tortuositas dapat dijadikan parameter untuk menentukan sifat anisotropik medium berpori dari perbandingan nilai tortuositas pada arah sumbu x, y, dan z.…”
unclassified
“…It is important not only in theory but in practice. Feranie S and other foreign scholars [6] calculated the fractal dimension of rock samples by scanning the rock slices ; Jiande Li and others [7] analyzed granite rock burst particulate debris under uniaxial and triaxial compression conditions with fractal theory then got a conclusion that clastic rock burst owns fractal characteristics; Liu Jinghong and others [8] did fractal research about the process that rock materials' crack expand to rupture ,which revealed microscopic fracture mechanism of crack from start, expansion to perforation and also proved that crack propagation process inside the material owns fractal characteristics, it also proved that destruction and instability of rock fracture is closely related to the distribution, start, expansion and perforation of microcracks inside . A large number of studies showed that: The fractal dimension is a good parameter in expressing the complexity of rock structure, however previous studies focused more on the macroscopic fracture structure and less on calculating the fractal dimension of microscopic cracks.…”
Section: Introductionmentioning
confidence: 98%